COVID-19 and the media in sub-Saharan Africa : media viability, framing and health communication - Dralega, Carol Azungi; Napakol, Angella (Emerald Publishing Limited, 2022)
As the global COVID-19 pandemic that broke out over two years ago is showing signs of relenting, and the world's attention draws towards yet another military conflict in Ukraine, the roles of crisis communication and media research couldn't be more critical. These roles, particularly in a post-truth and post-COVID era, call for new knowledge and enlightenment around discourses on: the infodemic of misinformation, information and communication rights, the role of online social networks, critical media literacy and the changes occuring in media and journalism ecosystems. Drawing on the region's distinct geo-political, economic, socio-cultural and technological contexts, COVID-19 and the Media in Sub-Saharan Africa brings together diverse interdisciplinary and multi-country perspectives, innovative methodologies as well rigorous theoretical and empirical analyses. The volume helps us deconstruct COVID-19 discourses on crisis communication and media developments focusing on three areas: Media viability, Framing and Health crisis communication. The chapters unpack issues on marginalisation, gender, media sustainability, credibility, priming, trust, sources, behavioural change, mental health, (mis)information, vaccine hesitancy and myths and more. Ultimately, this volume roots for sustainable and quality journalism, human (information and communication) rights, commitment to truth and efficacious (health) crisis communication. It is an excellent resource for academics, media industry, Journalism and media students, public health communication specialists, policy and advocacy groups in the region and globally.